Emission of the THz waves from large area mesas of superconducting Bi 2Sr2CaCu2O8+δ by the injection of spin polarized current - Turkoglu, F.; Ozyuzer, O.; Koseoglu, H.; Demirhan, Y.; Preu, Sascha; Malzer, Stefan; Simsek, Yilmaz; Wang, H.B.; Müller, Paul (Physica C-Superconductivity and Its Applications, 2013)
Rectangular Au/Co/Au/BiSrCaCuO (Bi2212) mesa structures with large areas and high thicknesses were fabricated on as-grown Bi2212 single crystals in order to obtain small critical current from as-grown mesas by the injection of spin polarized current and so eliminate the adjustment of doping level for successful THz emission. We have performed c-axis resistance versus temperature (R-T), current-voltage (I-V) characteristics and bolometer measurements. It is the first time that THz emission has been observed from as-grown mesas due to injection of spin polarized current. © 2013 Elsevier Ltd. All rights reserved.
Keywords: THz waves; Intrinsic Josephson junction; Bi2212; Spin polarized current

Enhancement of the critical current of intrinsic Josephson junctions by carrier injection - Kizilaslan, O.; Simsek, Yilmaz; Aksam, M.; Koval, Yury; Müller, Paul (Superconductor Science and Technology, 2015)
We present a study of the doping effect by carrier injection of high-Tc superconducting Bi-based whiskers. The current was injected in the c-axis direction, i.e., perpendicular to the superconducting planes. Superconducting properties were investigated systematically as a function of the doping level. The doping level of one and the same sample was changed by current injection in very small steps from an underdoped state up to a slightly overdoped state. We have observed that Tc versus log (jc) exhibits a dome-shaped characteristic, which can be fitted by a parabola. As Tc versus carrier concentration has a parabolic form, too, it can be concluded that the critical current density jc increases exponentially with the doping level. The electron-trapping mechanism is interpreted in the framework of Phillips' microscopic theory. In addition, the Joule heating effect in the intrinsic Josephson junction (IJJ) was controlled by carrier injection, and the effect of the non-equilibrium quasiparticle on the I-V curves of the IJJs was also discussed.
Keywords: carrier injection; intrinsic Josephson junction; superconductivity

Interferometer measurements of terahertz waves from Bi 2Sr 2CaCu 2O 8+d mesas - Turkoglu, F.; Koseoglu, H.; Demirhan, Y.; Ozyuzer, O.; Preu, Sascha; Malzer, Stefan; Simsek, Yilmaz; Müller, Paul; Yamamoto, T.; Kadowaki, K. (Superconductor Science & Technology, 2012)
We fabricated rectangular mesa structures of superconducting Bi Sr CaCu O (Bi2212) using e-beam lithography and Ar ion beam etching techniques for terahertz (THz) emission. c-axis resistance versus temperature (R-T), current-voltage (I-V) characteristics and bolometric THz power measurements were performed to characterize Bi2212 mesas. The emission frequency of mesas was determined using a Michelson interferometer setup which also demonstrates polarized emission. Interference patterns of THz radiation from Bi2212 mesas were detected by various detectors such as a liquid helium cooled silicon composite bolometer, a Golay cell and a pyroelectric detector. An emitted power as high as 0.06mW was detected from Bi2212 mesas. For the first time, most of the pumped power was extracted as THz emission from a Bi2212 mesa. The radiation at 0.54THz was detected using the Michelson interferometric setup. © 2012 IOP Publishing Ltd.

Resistive memory switching in layered oxides: A nB nO 3n+2 perovskite derivatives and Bi 2Sr 2CaCu 2O 8+δ high-T c superconductor - Koval, Yury; Chowdhury, Farzana; Jin, Xiaoyue; Simsek, Yilmaz; Lichtenberg, Frank; Pentcheva, Rossitza; Müller, Paul (physica status solidi (a), 2011)
Resistive memory switching was investigated in titanates and niobates of the type A B O and in the high-T superconductor Bi Sr CaCu O . We studied the switching by current injection perpendicular to the layers. Both dc and pulsed measurements were performed. Out-of-plane transport properties were investigated by measurements of the resistance and current-voltage characteristics (IVs) vs. temperature for different resistive states. The critical temperature of superconducting transition and the critical current of intrinsic Josephson junctions were also analyzed for different resistive states in Bi Sr CaCu O . The resistive memory switching was explained in terms of doping of the conducting layers, which is induced by trapped charges in the insulating layers. The charged insulating layers act as a floating gate and reduce or increase the carrier concentration in the conducting layers, respectively. We found that all studied materials demonstrate a different type of non-persistent resistive switching at low temperatures. This type of switching shows up in a specific form of current-voltage characteristics with a pronounced back-bending often called s-shaped IV. Both types of resistive switching with and without memory effect were analyzed in terms of electron overheating. We examine the role of hot electrons and discuss additional factors, which might lead to persistent resistive states. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: carrier injection; cuprate superconductors; current-voltage characteristics; perovskites; resistive memory switching; tunneling

Sequence of Quantum Phase Transitions in Bi2Sr2CaCu2 O8+δ Cuprates Revealed by in Situ Electrical Doping of One and the Same Sample - Jacobs, T.; Simsek, Yilmaz; Koval, Yury; Müller, Paul; Krasnov, Vladimir (Physical Review Letters, 2016)
Our recently discovered electrical doping technique allows a broad-range variation of carrier concentration without changing the chemical composition. We show that it is possible to induce superconductivity in a nondoped insulating sample and to tune it reversibly all the way to an overdoped metallic state. This way, we can investigate the whole doping diagram of one and the same sample. Our study reveals two distinct critical points. The one at the overdoped side is associated with the onset of the pseudogap and with the metal-to-insulator transition in the c-axis transport. The other at optimal doping is associated with the appearance of a "dressed" electron energy. Our study confirms the existence of multiple phase transitions under the superconducting dome in cuprates.

Superconductivity induced by carrier injection into non-superconducting Bi2Sr2CaCu2O8+δ - Simsek, Yilmaz; Koval, Yury; Gieb, Klaus; Müller, Paul (Superconductor Science and Technology, 2014)
Doping by carrier injection was investigated in strongly oxygen-depleted Bi2CaCu8 + δ. In order to perform four point c-axis measurements in non-superconducting samples, a new fabrication technique was developed. We were able to show that non-superconducting Bi 2CaCu8 + δ can be converted into a superconducting, even overdoped state only by applying a large bias current along the c-axis. A critical temperature of 91 K and a c-axis critical current density of 2000 A cm were achieved. Moreover, the doping effect is persistent and reversible resembling the resistive-memory switching effect observed earlier in various oxides. The mutual influence of oxygen doping and change of the charge carrier concentration by carrier injection is discussed. © 2014 IOP Publishing Ltd.
Keywords: Bi2212; charge carrier injection; doping; intrinsic Josephson junctions; superconductivity

Terahertz wave emission from intrinsic Josephson junctions in high- T c superconductors - Ozyuzer, L.; Simsek, Yilmaz; Koseoglu, H.; Turkoglu, F.; Kurter, C.; Welp, U.; Koshelev, A.; Gray, K.; Kwok, W.; Yamamoto, T.; Kadowaki, K.; Koval, Yury; et al. (Superconductor Science & Technology, 2009)
Recently, we experimentally demonstrated that rectangular mesa structures of intrinsic Josephson junctions (IJJ) in BiSrCaCu O (Bi2212) can be used as a compact solid-state generator of continuous, coherent and polarized terahertz (THz) radiation. In the present work, we will exhibit tall mesas (over 600 junctions) which were fabricated using UV lithography, e-beam lithography with photoresist and e-beam lithography with a Ti selective etching technique. We will present measurements of the c-axis resistance as a function of temperature and of current-voltage characteristics of THz emitting mesas with lateral sizes ranging from 30 × 300 to 100 × 300νm. Furthermore, we will discuss the dependence of the characteristics of the mesa structures on the oxygen doping level of the Bi2212 crystals. We will also experimentally show that the voltage-frequency relation of the ac Josephson effect has to match the cavity resonance for successful emission. © 2009 IOP Publishing Ltd.

Tuning superconductivity by carrier injection - Koval, Yury; Jin, Xiaoyue; C, Bergmann; Simsek, Yilmaz; Özyüzer, Lütfi; Müller, Paul; Wang, Huabing; Behr, Günter; Büchner, Bernd (Applied Physics Letters, 2010)
We have found that by extensive current injection along the c-axis, the superconducting properties of BiSrCaCu O can be changed effectively. We show that critical temperature, c-axis resistivity, and critical current of intrinsic Josephson junctions can be tuned in a large range from underdoping to extreme overdoping. This effect is reversible and persistent. Our results can be explained by trapping charges in the insulating layers, which induce a change of carrier concentration in superconducting planes. This floating gate concept can be a general property of layered materials where the insulating charge reservoir layers are separated from the conducting planes. © 2010 American Institute of Physics.